Studies of water quality on rives in Perlis - Nurul Huda Binti Abdullah (School of Environmental Engineering University Malaysia Perlis, 2011)
Environmental pollution problem especially water sources pollution become most of public interest. Rainfall water always content of mixtures of chemicals depends on the characteristic of rainfall area . This is because the rain always does the hydrology cycle with the surface water on the earth. Rain water will gather after the process of evaporation and evapotranspiration. Because of the rain fall, the characteristic of rainfall. this study wants to measure the water quality on Perlis river and from at least four different small rivers that connecting to Perlis river. The selected river that will be survey is Sungai Kuala Perlis, Sungai Kayang, Sungai Seriab, LencunganUtara River, Sungai Repoh and Sungai Kangar. It will give different quality and pollutant from each river. This plan will give easier way to investigate the sources of Pollutant comes from each river depend to the lifestyle from that area.